Motivation at work : A case study in Ammerchant Bank Berhad Sarawak / Chung Siew Mee @ Ellen Chung, Abang Sulaiman Abang Hj. Naim & Arrominy Hj. Arabi - Chung, Siew Mee @ Ellen Chung; Abang Hj. Naim, Abang Sulaiman; Hj. Arabi, Arrominy (2006)
Employee’s performance is frequently described as a joint function of ability and motivation, and one of the primary tasks facing a manager is motivating employees to perform to the best of their ability (Moorhead & Griffin, 1998). In fact, motivation has been described as “one of the most pivotal concerns of modem organizational research” (Baron, 1991: 1). But what exactly is work motivation? Pinder (1998) describes work motivation as the set of internal and external forces that initiate work-related behavior, and determine its form, direction, intensity, and duration. Work motivation is a middle-range concept that deals only with events and phenomena related to people in a work context. The definition recognizes the influence of both environmental forces (e.g., organizational reward systems, the nature of the work being performed) and forces inherent in the person (e.g., individual needs and motives) on work-related behavior.